Fostering Student's Character: Moral and Performance Dimensions in Madrasah - Ridho, Ali (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Abstract. In the contemporary global context, fostering religious and national moderation is critical for addressing complex international challenges. This manuscript explores the dual dimensions of moral and performance character within madrasas as potential solutions for fostering a harmonious and prosperous global society. Strengthening moral character, rooted in religious and national values, can facilitate intercultural dialogue and reduce conflict, while performance character, emphasizing integrity and a learner’s spirit, contributes to responsive governance and effective international cooperation. The manuscript argues that integrating these character dimensions within madrasa education enhances individual student development and builds a foundation for a stable and inclusive global community. A comprehensive review of philosophical, sociological, and educational perspectives highlights the importance of moral and performance character in shaping quality citizens capable of contributing positively to national and international spheres. The findings suggest that embedding these character dimensions in education systems can improve a country’s international standing and foster stronger global partnerships.